Educational orchestral how the object of scientific cognition is - M.S. Fylypchuk (Academy of Cognitive and Natural Sciences, 2007)
The important questions of methodological bases of functioning of training pops orchestra are considered. In the article The author approached the problem of teaching and education of students in the pops orchestra guiding by strong scientific knowledge's.